Infection, infection control, and disinfectants in a challenging infection era - Bowler, Philip G. (International Journal of Infection Control, 2021)
Health care-associated infections inflict a huge clinical and economic burden on public health worldwide. Bacterial resistance to antibiotics continues to escalate, and antimicrobial stewardship initiatives have yet to make a major impact. Additionally, the ability of bacteria to evade environmental threats by living within a self-produced protective biofilm and/or producing resistant spores further challenges effective infection control. The current severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic has also amplified the burden significantly. Amidst a particularly challenging infection era, the demand for meticulous infection control and prevention practices is paramount, a key component of which is the use of appropriate disinfectants that can combat a wide variety of microbial pathogens, including diverse forms of viruses and bacteria, particularly highly tolerant spore-forming and biofilm-forming microorganisms. This review addresses the advantages and disadvantages of commonly used disinfectants such as alcohols, hypochlorite, and quaternary ammonium compounds, together with oxidizing agents such as chlorine dioxide and peracetic acid, which are gaining increasing acceptance in routine infection control practices today. Given the increasing requirements for rapid-acting disinfectants that are effective against the toughest of microorganisms (e.g. spores and biofilm), are environmentally friendly, and remain active under diverse environmental conditions, emerging oxidizing agents warrant further consideration, particularly chlorine dioxide, which offers most requirements for an ideal disinfectant, including retention of activity over a broad pH range. Given the critical importance of infection control and antimicrobial stewardship in public health and health care facilities today, consideration of chlorine dioxide as a safe, selective, highly effective, and environmentally friendly disinfectant is warranted.